Some inconsistencies in the current regulation of the right of establishment of companies - Contaldi, Gianluca (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
In a recent ruling, the Court of Justice once again addressed the issue of the freedom of establishment of companies and its relationship with national rules of Private International law. Although the decision is nothing new, it urgently raises the issue of the protection of persons who may be affected by a transfer of the seat abroad or by a change in the applicable law, such as creditors, minority shareholders and employees.The situation has become even more complicated because, following the ruling of the Court of Justice in the Polbud case and Directive 2019/2121, there are now two different ways for companies to exercise their right of establishment. These different modes, although clearly distinct from a legal point of view, are poorly coordinated precisely from the point of view of the protection of those who had relied on a particular legal asset of the company. In order to resolve this aporia, the European Institutions should intervene by completing the regulatory harmonisation of the sector or by adopting a regulation (so-called Rome V) on the law applicable to companies.
Keywords: Freedom of establishment of companies; rules of private international law on companies; incorporation; mandatory provisions